THE MANAGEMENT OF PUBLIC RELATION OF ISLAMIC HIGHER EDUCATION IN THE ORGANIZATIONAL IMAGING (A Comparative Study of UIN of North Sumatra Medan and UIN of Syarif Hidayatullah Jakarta) - Nurhanifah Nurhanifah; Tengku Walisya (State Islamic University of North Sumatra Indonesia, 2019)
This study seeks to conduct a comparative study of public relations management at UIN North Sumatra and Syarif Hidayatullah UIN Jakarta in an effort to build a positive image of the institution. This research is conducted with qualitative methods with data collection techniques through interviews, documentation and observation. The findings of public relations management research, those are, first, in the planning of Public Relation of the State Islamic Higher Educations in its organizational imaging, there are differences planning that have been made by UIN of North Sumatra Medan and UIN of Syarif Hidayatullah Jakarta. UIN of North Sumatra Medan has is doing a public relations with has no evidence of performance that supports the university's vision and mission. While UIN of Syarif Hidayatullah Jakarta’s public relations prioritizes planning work programs that support the university's vision and mission. The second, there are differences between UIN of North Sumatra’s public relations program and UIN of Syarif Hidayatullah Jakarta. In terms of implementing work programs, UIN of Syarif Hidayatullah Jakarta’s public relations is more advanced and better equipped to carry out work programs. It could be said that UIN of Syarif Hidayatullah Jakarta’s public relations is more established and professional. Thirdly, the public relations of UIN of Syarif Hidayatullah Jakarta requires the addition of quality human resources. While the public relations of UIN of North Sumatra Medan requires the addition of public relations facilities and funding. That is the presence of public relations is not a rigid structural unit because it is bound by procedures under the leadership or at least there is a direct relationship to the leadership. Experts in one field of public relations are needed. Good coordination is needed. UIN of North Sumatra Medan and UIN of Syarif Hidayatullah Jakarta need to optimize public relation to build a positive image of the institution, public relations work needs to be handled by a competent expert. The last, public relations needs a separate institution to be more dynamic in carrying out its functions. Keywords: Public Relation, Organizational Imaging, UIN of North Sumatra Medan, UIN of Syarif Hidayatullah Jakarta